Which contextual and sociocultural information predict irony perception?. Issue 3 (15th March 2020) - Rivière, Elora; Champagne-Lavau, Maud
ABSTRACT: The present study in French sought to investigate which factors predict irony perception most efficiently. An experiment was developed following three steps. The first two steps focused on the creation of stimuli to be evaluated in the third step. In this last step, participants, whose sociocultural characteristics (gender, age, and level of education) were taken into account as factors, evaluated utterances according to their level of irony and the presence of contextual factors (i.e., allusion to a failed expectancy, negative tension, and presence of a victim). The absence or presence of a lexical marker in the utterances was also a controlled factor. The main results revealed contextual factors as the strongest predictors of irony perception, but also pointed out the not inconsiderable role played by the sociocultural factors (gender and level of education) of the participants.